2023
DOI: 10.14309/ctg.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors Increase the Risk of Nonsteroidal Anti-inflammatory Drug-Related Small-Bowel Injury: A Systematic Review With Meta-analysis

Abstract: INTRODUCTION: Conflicting results exist on the association between proton-pump inhibitor (PPI) and nonsteroidal anti-inflammatory drug (NSAID)-related small-bowel damage. The aim of this study was to determine whether PPIs increased the risk of NSAID-related small-bowel damage by meta-analysis. METHODS: A systematic electronic search in PubMed, Embase, and Web of Science was conducted from the time the database was created until March 31, 2022, for stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…The prophylactic use of omeprazole in combination with NSAIDs is often considered in practice to be a benign treatment that is more likely to be helpful than harmful ( 35 ). However, the scientific evidence does not currently support this recommendation ( 2 , 10 , 36 ) and the co-administration of PPIs with NSAIDs may in fact increase the risk of NSAID-induced intestinal injury by inducing intestinal dysbiosis in people ( 37 ) and in dogs treated with piroxicam ( 35 ). The exact mechanism for this is not well understood, but the effects of PPIs on the gastrointestinal microbiome contributing to increased cytotoxicity of bile and exacerbation of mucosal injury have been postulated ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prophylactic use of omeprazole in combination with NSAIDs is often considered in practice to be a benign treatment that is more likely to be helpful than harmful ( 35 ). However, the scientific evidence does not currently support this recommendation ( 2 , 10 , 36 ) and the co-administration of PPIs with NSAIDs may in fact increase the risk of NSAID-induced intestinal injury by inducing intestinal dysbiosis in people ( 37 ) and in dogs treated with piroxicam ( 35 ). The exact mechanism for this is not well understood, but the effects of PPIs on the gastrointestinal microbiome contributing to increased cytotoxicity of bile and exacerbation of mucosal injury have been postulated ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 74% of patients received PPI during hospital stay. An important finding to increase awareness among clinicians of appropriate use of PPI as a systematic review and meta-analysis showed an increased risk of small bowel damage using this medication in patients taking nonsteroidal anti-inflammatory drug (NSAID) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%